2004
DOI: 10.1194/jlr.m400036-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Participation of macrophages in atherosclerotic lesion morphology in LDLr−/− mice

Abstract: Lyst beige (beige) mice crossed with LDL receptordeficient (LDLr ؊ / ؊ ) mice had a distinct atherosclerotic lesion morphology that was not observed in LDLr ؊ / ؊ mice. This morphology is often associated with a stable plaque phenotype. We hypothesized that macrophage expression of the beige mutation accounted for this distinct morphology. Cultured bone marrow-derived macrophages from LDLr ؊ / ؊ and beige,LDLr ؊ / ؊ mice were compared for their ability to accumulate cholesterol, efflux cholesterol, migrate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…html). Results were reported as a percentage of the total aortic area that contained lesions ( 11 ).…”
Section: Downloaded Frommentioning
confidence: 99%
“…html). Results were reported as a percentage of the total aortic area that contained lesions ( 11 ).…”
Section: Downloaded Frommentioning
confidence: 99%
“…In parallel, collagen content and collagen gene expression were increased. Schiller et al [74] demonstrated macrophage rich and collagen poor lesions in the aortic roots of irradiated LDLR -/-mice after acute high dose (10 Gy) total body irradiation.…”
mentioning
confidence: 99%
“…Atherosclerotic plaques in mice are regarded as resistant to rupture, and the relevance of mouse studies to model the final events precipitated by plaque disruption of human atherosclerotic lesions is controversial (21,22). Nevertheless, a previous report from our laboratory documented changes in plaque composition that define the double mutant BgLDLr 2/2 mouse, which resemble the characteristics of a more stable type of human lesion (10). Therefore, the present study was designed to identify features/mechanisms that control plaque stability in mice with the beige phenotype.…”
Section: Discussionmentioning
confidence: 98%
“…BM macrophages were cultured as described previously (10). After 5-7 days of culture, cells were harvested with Versene (Gibco), pooled for each mouse, counted, and seeded at ?2 3 10 6 cells per well onto six-well plates.…”
Section: Primary Cell Culturementioning
confidence: 99%
See 1 more Smart Citation